Specific volatiles of tea plants determine the host preference behavior of Empoasca onukii - Chen, Feng; Huang, Peng; Wang, Jun; Wu, Wei; Lin, Yong-Wen; Hu, Jin-Feng; Liu, Xin-Gang (Frontiers in Plant Science, 2023)
Empoasca onukii is a major pest that attacking attacks tea plants. To seek effective and sustainable methods to control the pest, it is necessary to assess its host preference among different species of tea species and understand the critical factors of behind this behavior. In this study, the behavioral preference of E. onukii to for volatile organic compounds (VOCs) of three potted tea species were was evaluated. The VOCs released by the three tea species were analyzed using gas chromatography-mass spectrometryGC-MS, and the major components were used to test the pest's preference. Based on the tTranscriptome analysesanalysis was used to, we inferred the key genes that affect the biosyntheses of those VOCs. The results showed that the tendency of E. onukii toward the VOCs of the three tea species was the strongest in green tea, followed by white tea, and the weakest in red tea. This behavioral preference was significantly and positively correlated with the relative contents levels of hexanol, linalool, and geraniol in tea volatiles. In these three tea species, the rRelative content of hexanol was significantly and positively correlated with the expression of genes TEA009423 (LOX2.1), TEA009596 (LOX1.5), TEA008699 (HPL), TEA018669 (CYPADH), and TEA015686 (ADHIII), and. the relative Relative content of linalool was significantly and positively correlated with the expression of genes TEA001435 (CAD) and Camellia_sinensis_newGene_22126 (TPS). Moreover, Rthe relative content of geraniol was significantly and positively correlated with the expression of genes TEA001435 (CAD), TEA002658 (CYP76B6), TEA025455 (CYP76T24), and Camellia_sinensis_newGene_22126 (TPS). The above findings suggested that three volatiles (hexanol, linalool, and geraniol) determined the behavioral preference of E. onukii toward tea plants, and their biosyntheses biosynthesis might beiwas mainly affected by nine genes (TEA009423,